ATYPICAL PRESENTATION OF FUNCTIONING MALIGNANT METASTATIC PARAGANGLIOMA WITH RECURRENT MYASTHENIA CRISIS - MM, Nur Hidayah; MA, Masliza Hanuni; WA, Siti Sanaa; Azmi, Khairul; MU, Hadzfadzila; Noor I, Mohd (Journal of the ASEAN Federation of Endocrine Societies, 2023)
INTRODUCTION/BACKGROUND The crude prevalence of paraganglioma is 2 per 100,000 persons/year. Roughly 10% of paragangliomas are malignant, resulting in a rare occurrence of 90-95 cases per 400 million people. The usual symptom of paraganglioma is related to catecholamine hypersecretion. However, we report an intra-abdominal paraganglioma presenting as recurrent myasthenia crisis without symptoms of catecholamine hypersecretion. CASE We report a case of a 34-year-old female who presented with abdominal pain. On work-up, CT scan revealed a 20- cm intraabdominal mass. Inguinal lymph nodes biopsy revealed reactive tissue. She was then lost to follow-up. She had recurrent admission for myasthenia crisis after 6 months of initial presentation. She received regular plasma exchange during the crisis to which she responded well. Further work-up of the abdominal mass revealed a functioning abdominal paraganglioma. Throughout her hospitalization, patient was normotensive with no symptoms to suggest paroxysm. CT of the thorax-abdomen-pelvis revealed a 27-cm intraabdominal multilobulated mass encasing major abdominal vessels and causing mass effect to adjacent organs. There was also compression fracture with lytic lesions of L3 and L4 vertebra. No mediastinal mass was seen. 24-hr urine metanephrines (umol/day): normetanephrine 21.9 (0.0- 2.13), metanephrine 200.0 (0.0-1.62), 3-methoxytyramine 251.40 (0.10–1.79). Cervical lymph nodes tissue-biopsy revealed histological features and immunohistochemistry staining in favour of paraganglioma with necrosis and high mitotic figures. A multi-disciplinary-team discussion was done with surgical, oncology and radio-nuclear for direction of therapy. Unfortunately, debulking surgery was not feasible in view of the large functioning mass encasing major vessels. Chemo- and radio-nuclear therapy is not suitable in view of baseline ECOG-4. Decision for best supportive care was made with family members. CONCLUSION Due to its low prevalence, there is a low index of suspicion when it comes to diagnosing paraganglioma. Adding atypical presentation to this, this may lead to delay diagnosis and treatment. Early diagnosis is utmost important in a case of malignant paraganglioma since the treatment is by surgical removal.